The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12879-019-4017-0
|View full text |Cite
|
Sign up to set email alerts
|

Influenza epidemiology and influenza vaccine effectiveness during the 2015–2016 season: results from the Global Influenza Hospital Surveillance Network

Abstract: Background The Global Influenza Hospital Surveillance Network is an international platform whose primary objective is to study severe cases of influenza requiring hospitalization. Methods During the 2015–2016 influenza season, 11 sites in the Global Influenza Hospital Surveillance Network in nine countries (Russian Federation, Czech Republic, Turkey, France, China, Spain, Mexico, India, and Brazil) participated in a prospective, active-surveillance, hospital-based epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
2
15
0
1
Order By: Relevance
“…[8][9][10][11][12][13][14] A study has shown the influenza vaccine also provided low-to-moderate protection against hospitalization with influenza virus infection. 2 Reductions of 13% of preterm births and 26% of low birth weight were reported, 8,9,15 but no effect on small for gestational age was reported. 16 The safety of influenza vaccination during pregnancy was determined through post-licensure vaccine safety monitoring platforms: pregnancy exposure registries; active and passive surveillance systems; and observational studies.…”
Section: Backg Rou N Dmentioning
confidence: 98%
See 2 more Smart Citations
“…[8][9][10][11][12][13][14] A study has shown the influenza vaccine also provided low-to-moderate protection against hospitalization with influenza virus infection. 2 Reductions of 13% of preterm births and 26% of low birth weight were reported, 8,9,15 but no effect on small for gestational age was reported. 16 The safety of influenza vaccination during pregnancy was determined through post-licensure vaccine safety monitoring platforms: pregnancy exposure registries; active and passive surveillance systems; and observational studies.…”
Section: Backg Rou N Dmentioning
confidence: 98%
“…Pregnant women are at increased risk of hospitalization due to influenza compared with both the general population and women of childbearing age, although there is inconsistent and limited evidence that influenza virus infection causes adverse pregnancy outcomes . While some studies have reported little or no increased risk of preterm birth among women who were hospitalized with influenza during pregnancy, others found an approximately four‐fold increased risk of preterm birth .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumonia is a major complication of in uenza that may be associated with mortality, other common complications arise due to exacerbation of chronic medical issues, while cardiac and neurological complications e.g. encephalitis are rare [23,24]. Known risk factors for complications of in uenza include: older age, preexisting cardiopulmonary disease, immunosuppression, obesity, neurological and other common medical conditions [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…8 Data in the post-pandemic era generally showed that A(H1N1)pdm09 was associated with younger patients and greater severity compared to A(H3N2). [9][10][11][12][13] However, some inconsistencies exist due to heterogeneous setting of each study such as different participated countries, healthcare resources, vaccination rates, and other potential confounders. Therefore, we pursue to reveal more clear evidence of difference between influenza A subtypes with minimizing confounders in highly vaccinated, well-developed single country, South Korea.…”
Section: Backg Rou N Dmentioning
confidence: 99%